2010
DOI: 10.1371/journal.pone.0012833
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Attenuation of Auxin-Mediated Bimodality in Lateral Root Formation Is Partly Coupled by the Heterotrimeric G Protein Complex

Abstract: BackgroundAuxin and glucose are both essential elements in normal root development. The heterotrimeric G protein complex in Arabidopsis thaliana, defined as containing alpha (AtGPA1), beta (AGB1), and gamma (AGG) subunits and a GTPase accelerating protein called Regulator of G Signaling 1 protein (AtRGS1), are involved in glucose signaling and regulate auxin transport.Methodology/Principal FindingsA systems approach was used to show that formation of lateral roots, a process requiring coordinated cell division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…The BR signaling pathway has been reported to influence the functions of auxin and vice versa during root growth and development (Nemhauser et al, 2004;Mouchel et al, 2006;Hardtke et al, 2007;Vert et al, 2008). Similarly, sugar signals are also reported to interact with the auxin signaling machinery (Moore et al, 2003;Gonzali et al, 2005;Ohto et al, 2006;Mishra et al, 2009;Mudgil et al, 2009;Booker et al, 2010;Sairanen et al, 2012;Yuan et al, 2014). Glc inhibits the G-protein complex-dependent Figure 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BR signaling pathway has been reported to influence the functions of auxin and vice versa during root growth and development (Nemhauser et al, 2004;Mouchel et al, 2006;Hardtke et al, 2007;Vert et al, 2008). Similarly, sugar signals are also reported to interact with the auxin signaling machinery (Moore et al, 2003;Gonzali et al, 2005;Ohto et al, 2006;Mishra et al, 2009;Mudgil et al, 2009;Booker et al, 2010;Sairanen et al, 2012;Yuan et al, 2014). Glc inhibits the G-protein complex-dependent Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested a prominent effect of Glc on root growth and development in Arabidopsis (Mishra et al, 2009;Booker et al, 2010;Kircher and Schopfer, 2012;Xiong et al, 2013;Yuan et al, 2014). Increasing Figure 1.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…reports for sugar and auxin interaction during plant growth and development (Moore et al, 2003;Mishra et al, 2009;Mudgil et al, 2009;Booker et al, 2010). To determine any involvement of auxin machinery in Glc-BR control of etiolated hypocotyl elongation growth, we used well-established auxin reporter auxin responsive promoter DR5::GUS.…”
Section: Involvement Of Auxin-signaling Components In Controlling Hypmentioning
confidence: 99%
“…Increasing Glc concentrations can induce differential root length, lateral roots, gravitropism, and root hair elongation in auxin perception and signaling mutants, suggesting that auxin signaling is involved in controlling Glc-regulated root responses (Mishra et al, 2009). Glc has also been shown to act via G-protein signaling to attenuate auxin-mediated bimodality in controlling lateral root formation (Booker et al, 2010).…”
mentioning
confidence: 99%